Expertise, neoliberal governmentality and the outsourcing of Health and Physical Education. Issue 2 (3rd March 2020) - Enright, Eimear; Kirk, David; Macdonald, Doune
ABSTRACT: As new markets and opportunities for profit are being sought within and around schools, boundaries between private and public, profit and philanthropy are blurring and the boundaries that circumscribe knowledge and expertise are being reconstituted. This paper considers how expertise is constituted when curriculum work is outsourced to new actors in the Global Education Industry (GEI). Our findings suggest that, in the context of the GEI, conventional understandings of expertise are problematic. Our data show that under conditions of neoliberalisation and in relation specifically to the outsourcing of Health and Physical Education, expertise was distributed and expressed in at least four forms: personal experiential knowledge; artefacts and resources; professional expertise (such as teaching) within partnerships as forms of extended complementarity; and the application of science and reverence for research evidence. We advocate for a reconceptualisation of expertise in education in ways that recognise its personal, relational and material nature.